1988
DOI: 10.1002/j.1460-2075.1988.tb02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human EGF receptor with ligand-stimulatable kinase activity in insect cells using a baculovirus vector.

Abstract: The mechanism by which the binding of epidermal growth factor (EGF) to specific cell surface receptors induces a range of biological responses remains poorly understood. An important part of the study of signal transduction in this system involves the production of sufficient native and mutant EGF receptor species for X‐ray crystallographic and spectroscopic analysis. Baculovirus vectors containing the cDNA encoding the human EGF receptor protein have here been utilized to infect insect cells. This results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
3
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 40 publications
4
50
3
2
Order By: Relevance
“…However, although SRK was correctly inserted into the membrane, with the C terminus extending into the cytoplasm, the majority of the recombinant SRK was not targeted to the plasmalemma of the insect cells. This finding contrasts with results obtained for animal receptor kinases, such as epidermal growth factor receptor or insulin receptor, which have been shown to be correctly addressed to the plasmalemma when expressed in insect cells (34,35). Nevertheless, it is worth noting that plant K ϩ channels, which are plasma membrane proteins, also were retained mainly in the internal cellular membranes when expressed in the insect cell͞baculo-virus system (36,37).…”
Section: Discussioncontrasting
confidence: 60%
“…However, although SRK was correctly inserted into the membrane, with the C terminus extending into the cytoplasm, the majority of the recombinant SRK was not targeted to the plasmalemma of the insect cells. This finding contrasts with results obtained for animal receptor kinases, such as epidermal growth factor receptor or insulin receptor, which have been shown to be correctly addressed to the plasmalemma when expressed in insect cells (34,35). Nevertheless, it is worth noting that plant K ϩ channels, which are plasma membrane proteins, also were retained mainly in the internal cellular membranes when expressed in the insect cell͞baculo-virus system (36,37).…”
Section: Discussioncontrasting
confidence: 60%
“…Proteins in medium (supplemented with 10% fetal calf serum) or cell lysates prepared as described [21] were separated on a 15% SDS/polyacrylamide gel. Molecular mass markers were stained with Coomassie brilliant blue R. Electrophoretic transfer of proteins was performed essentially according to the method of Burnette [22].…”
Section: Western Blotsmentioning
confidence: 99%
“…Several studies have reported that oligosaccharide structures synthesized by insect cells differ from those synthesized by mammalian cells (Butters & Hughes, 1981 ;Hsieh & Robbins, 1984;Weber et al, 1986;Wojchowski et al, 1987;Greenfield et al, 1988;Kuroda et al, 1990;Wathen et al, 1991). In particular, insect cells appear not to process highmannose precursor oligosaccharides into mammaliantype complex structures.…”
Section: Introductionmentioning
confidence: 99%